Mild Traumatic Brain Injuries and Risk for Affective and Behavioral Disorders - Delmonico, Richard L.; Tucker, Lue-Yen; Theodore, Brian R.; Camicia, Michelle; Filanosky, Charles; Haarbauer-Krupa, Juliet (Pediatrics (Evanston), 2024)
Recent studies document an association between mild traumatic brain injuries (mTBIs) in children and postinjury psychiatric disorders. However. these studies were subject to limitations in the design, lack of long-term follow-up, and poorly defined psychiatric outcomes. This study determines the incidence and relative risk of postinjury new affective and behavior disorders 4 years after mTBIs. A cohort study of mTBI cases and matched comparisons within an integrated health care system. The mTBI group included patients ≤17 years of age, diagnosed with mTBI from 2000 to 2014 (N = 18 917). Comparisons included 2 unexposed patients (N = 37 834) per each mTBI-exposed patient, randomly selected and matched for age, sex, race/ethnicity, and date of medical visit (reference date to mTBI injury). Outcomes included a diagnosis of affective or behavioral disorders in the 4 years after mTBI or the reference date. Adjusted risks for affective disorders were significantly higher across the first 3 years after injury for the mTBI group, especially during the second year, with a 34% increase in risk. Adjusted risks for behavioral disorders were significant at years 2 and 4, with up to a 37% increase in risk. The age group with the highest risk for postinjury affective and behavioral disorders was 10- to 13-year-old patients. Sustaining an mTBI significantly increased the risks of having a new affective or behavioral disorder up to 4 years after injury. Initial and ongoing screening for affective and behavior disorders following an mTBI can identify persistent conditions that may pose barriers to recovery.